Quantitative proteomics revealed modulation of macrophages by MetQ gene of Streptococcus suis serotype 2 - Pei, Xiaomeng (AMB Express, 2020)
Streptococcus suis serotype 2 (SS2) is a serious zoonotic pathogen; it can lead to symptoms of streptococcal toxic shock syndrome (STSS) in humans and sepsis in pigs, and poses a great threat to public health. The SS2 MetQ gene deletion strain has attenuated antiphagocytosis, although the mechanism of antiphagocytosis and pathogenesis of MetQ in SS2 has remained unclear. In this study, stable isotope labeling by amino acids in cell culture (SILAC) based liquid chromatography–mass spectrometry (LC–MS) and subsequent bioinformatics analysis was used to determine differentially expressed proteins of RAW264.7 cells infected with △MetQ and ZY05719. Proteomic results were verified by quantitative real-time polymerase chain reaction (qRT-PCR) and Western blotting for selected proteins. Further research was focused mainly on immune system processes related to downregulated proteins, such as Src and Ccl9, and actin cytoskeleton and endocytosis related upregulated proteins, like Pstpip1 and Ppp1r9b. The proteomic results in this study shed light on the mechanism of antiphagocytosis and innate immunity of macrophages infected with △MetQ and ZY05719, which might provide novel targets to prevent or control the infection of SS2.